2005
DOI: 10.1161/01.hyp.0000158259.68614.40
|View full text |Cite
|
Sign up to set email alerts
|

Hyperadrenergic Postural Tachycardia Syndrome in Mast Cell Activation Disorders

Abstract: Abstract-Postural tachycardia syndrome (POTS) is a disabling condition that commonly affects otherwise normal young females. Because these patients can present with a flushing disorder, we hypothesized that mast cell activation (MCA) can contribute to its pathogenesis. Here we describe POTS patients with MCA (MCAϩPOTS), diagnosed by episodes of flushing and abnormal increases in urine methylhistamine, and compared them to POTS patients with episodic flushing but normal urine methylhistamine and to normal healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
124
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 21 publications
3
124
0
3
Order By: Relevance
“…34 Both drugs can cause drowsiness, fatigue and worsen mental clouding. Modafinil might help the fatigue and cognitive dysfunction seen in some patients 35 with only a minimal increase in tachycardia.…”
Section: Treatmentmentioning
confidence: 99%
“…34 Both drugs can cause drowsiness, fatigue and worsen mental clouding. Modafinil might help the fatigue and cognitive dysfunction seen in some patients 35 with only a minimal increase in tachycardia.…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, there must be a recorded rise in urine or serum levels of mast cell degranulation markers, and the condition must be responsive to antimediator therapy such as histamine 1 and 2 receptor antagonists, leukotriene antagonists, and mast cell stabilizers [1]. A proportion of patients with ncMCAS also have concomitant postural orthostatic tachycardia syndrome (POTS) [2]. POTS is a heterogenous form of orthostatic intolerance characterized by an increase in the heart rate of at least 30 bpm within 10 minutes of assuming an upright posture.…”
mentioning
confidence: 99%
“…POTS commonly presents with cardiac symptoms (eg, palpitations, lightheadedness, and dyspnea) and noncardiac symptoms (eg, headache, exercise intolerance, fatigue) [3]. The link between these 2 clinical entities is not entirely clear, although it has been suggested that the vasodilator effect of MCA-related mediators such as histamine, norepinephrine, and neuropeptide Y (NPY) results in increased sympathetic activity, which in turn leads to orthostatic tachycardia [2]. In recent years, a handful of patients with recalcitrant ncMCAS were successfully treated with omalizumab, the monoclonal antibody to IgE [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in this "crossover" group of patients, the OHT manifested as either a persistent hypertensive response to upright posture or as a hypertensive crisis with upright BP as high as 240/140. 4 Patients presenting with acute baroreflex failure experience some of the highest blood pressures encountered in contemporary practice, sometimes with surges of Ͼ300 mm Hg. 5 In subsequent days and weeks, the surges moderate, but substantial OHT may continue, although it usually declines somewhat with continued upright posture.…”
mentioning
confidence: 99%